Intraductal papillary mucinous neoplasm of the pancreas: diagnostic performance of the 2017 international consensus guidelines using CT and MRI - Min, Ji Hye; Kim, Young Kon; Kim, Seon Kyoung; Kim, Honsoul; Ahn, Soohyun (European Radiology, 2021)
Objectives: To assess the diagnostic performance of the 2017 international consensus guidelines for intraductal papillary mucinous neoplasm (IPMN) of the pancreas and to compare the diagnostic performance and intermodality agreement between contrast-enhanced CT and MRI. Methods: We retrospectively evaluated patients with surgical resection of IPMN of the pancreas who underwent preoperative CT and MRI between 2009 and 2019. Two radiologists evaluated the clinical and imaging features of IPMN of pancreas according to the 2017 international consensus guideline. Univariable and multivariable analyses were performed to identify significant predictors of malignancy in IPMN. The diagnostic abilities of CT and MRI were compared, and their intermodality agreement was determined. Results: Of 175 patients (mean age, 64 years; 116 males), 88 (50.3%) had malignant IPMN. On multivariable analysis, all three high-risk stigmata (main pancreatic duct [MPD] ≥ 10 mm, mural nodule ≥ 5 mm, and obstructive jaundice) and two worrisome features (MPD 5–9 mm and elevated carbohydrate antigen 19–9) were associated with malignant IPMN on CT and MRI (p < 0.05). A mural nodule < 5 mm on MRI was also associated with malignant IPMN (OR 5.3, p = 0.009). The diagnostic accuracy of high-risk stigmata showed no difference between CT and MRI (73.7% vs. 75.4%, p = 0.505), with good to excellent intermodality agreement. Conclusions: Current high-risk stigmata had the strongest association with malignant IPMN on CT and MRI. Although MRI is superior to CT for identifying mural nodules, diagnostic performance for differentiating malignant from benign IPMNs was similar between CT and MRI. Key Points: • The current high-risk stigmata in the 2017 International Consensus Guidelines had the strongest association with malignant IPMN on CT and MRI. • MRI is better than CT for identifying enhancing mural nodule. • Diagnostic performance for differentiating malignant from benign IPMNs was similar between CT and MRI.
Keywords: Carcinoma, Pancreatic Ductal; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Pancreas; Pancreatic Neoplasms; Retrospective Studies; Tomography, X-Ray Computed; Magnetic resonance imaging; Multidetector computed tomography; Pancreatic intraductal neoplasms